Astrocytes produce IL‐19 in response to bacterial challenge and are sensitive to the immunosuppressive effects of this IL‐10 family member. Issue 5 (14th February 2014) - Cooley, Ian D.; Chauhan, Vinita S.; Donneyz, Miguel A.; Marriott, Ian
<x xml:space="preserve">Abstract</x> There is growing appreciation that resident glial cells can initiate and/or regulate inflammation following trauma or infection in the central nervous system (CNS). We have previously demonstrated the ability of microglia and astrocytes to respond to bacterial pathogens or their products by rapid production of inflammatory mediators, followed by the production of the immunosuppressive cytokine interleukin (IL)−10. IL‐19, another member of the IL‐10 family of cytokines, has been studied in the context of a number of inflammatory conditions in the periphery and is known to modulate immune cell activity. In the present study, we demonstrate the constitutive and/or inducible expression of IL‐19 and its cognate receptor subunits, IL‐19Rα and IL‐19Rβ (also known as IL‐20R1 and IL‐20R2, and IL‐20RA and IL‐20RB), in mouse brain tissue, and by primary murine and human astrocytes. We also provide evidence for the presence of a novel truncated IL‐19Rα transcript variant in mouse brain tissue, but not glial cells, that shows reduced expression following bacterial infection. Importantly, IL‐19R functionality in glia is indicated by the ability of IL‐19 to regulate signaling component expression in these cells. Furthermore, while IL‐19 itself had no effect on glial cytokine production, IL‐19 treatment of bacterially infected or Toll‐like receptor ligand stimulated astrocytes significantly attenuated pro‐inflammatory cytokine production. The bacterially induced production of IL‐19 by these resident CNS cells, the constitutive expression of its cognate receptor subunits, and the immunomodulatory effects of this cytokine, suggest a novel mechanism by which astrocytes can regulate CNS inflammation. GLIA 2014;62:818–828